Conjugate Heat Transfer in a Differentially Heated Porous Cavity Filled with Nanofluid - Ismael, Muneer A.; Mahdi, Ahmed Abdulkareem (Basrah Journal for Engineering Sciences, 2013)
The conjugate natural convection-conduction heat transfer in a domain composed of nanofluids filled porous cavity heated by a vertical solid wall is studied under steady-state conditions. The vertical left wall of the solid is kept isothermal at hot temperature Th. The vertical right wall of the solid is in contact with the nanofluid saturated porous medium contained in the cavity. The right vertical wall of the cavity is kept isothermally at the lower temperature Tc. The upper and lower horizontal walls are kept adiabatic. The governing equations of the heat transfer in the solid wall and heat and nanofluid flow, based on the Darcy model, in the nanofluid-saturated porous medium together with the derived relation of the interface temperature are solved numerically using the over-successive relaxation finite- difference method. A temperature independent nanofluids properties model is adopted. The investigated parameters are the nanoparticles volume fraction  (0-0.2), Rayleigh number Ra (10-1000), solid wall to base-fluid saturated porous medium thermal conductivity ratio kwf (0.1, 1, 10), and the solid wall thickness D (0.05-0.5). The results are presented in the conventional form; contours of streamlines and isotherms and the average Nusselt number. At a very low Rayleigh number Ra=10, an enhancement in heat transfer within the porous cavity with  is observed. Otherwise, the heat transfer may be unchanged or deteriorated with  depending on the wall thickness D and the conductivity ratio kwf.